Instructional Video using Wondershare Filmora 9 in the Interpretive Reading Course for English Language Education Students - Ni Made Yuniari; I Gusti Ayu Indah Triana Juliari (Universitas Pendidikan Ganesha, 2021)
The Covid-19 pandemic has had a significant impact on education. The implementation of online learning results in the lack of availability of appropriate learning media to support the implementation of online learning. This study aims to develop learning videos using Wondershare Filmora 9 in the Interpretive Reading course for third semester students of English Education. The development of this learning video uses the ADDIE development model which consists of the analysis, design, development, implementation, and evaluation stages. The results of the validity of interactive multimedia development will be presented with two main points which include: subject matter experts, and learning media experts. The subjects of this research include experts, namely 2 subject experts, and 2 learning media experts. The method used in collecting data is the observation method, interview method, and questionnaire method. The data analysis technique in this research is descriptive qualitative and descriptive quantitative. The data collection instrument in this study was using a questionnaire. The results of the validation carried out by material experts I and II were 93.84%, while the results of the validation carried out by media experts I and II were 87.05%. It can be concluded that the learning video that has been developed with the help of Wondershare Filmora 9 is very suitable for use in interpretive reading courses. Based on these results and conclusions, learning videos can be used as an alternative in overcoming the problem of the lack of media availability in online learning.